Physical Fitness and Depression Among Older People: The Differences Between Elderly Women Living in Community and Institutionalized - Murugan, Karthiga; Theng, Ng Li; Jamaludin, Jeniza; Abdul Rahman, Normy Rafida (2025)
Reduced fitness strength is one of the risk factors of depression occurred in elderly. The prevalence of depression in the nursing home population is very high compared to community-dwelling population. The aim of this study is to measure physical fitness performance of elderly women living in community compared to elderly women living in institutionalized, depression rate of elderly women living in community compared to elderly women living in institutionalized, and the relationship between physical fitness and depression among the community-dwelling elderly women and institutionalized elderly women. A total of 71 female aged 60 years above participated, 58 from the community, 8 from elderly home, and 5 from nursing home. Cross-sectional and correlation study were designed. Senior fitness test and Geriatric Depression Scale (GDS)-Short Form were used. Statistical analysis was conducted using Kolmogorov-Smirnoff test (p>0.05), Independent Sample T-tests (p<0.05), and Spearman correlation. Results of the study showed that the institutionalized elderly women have poorer physical fitness performance compared to community-dwelling elderly women, while depression rate of elderly women in community are lower than the depression rate of elderly women in the institution. The elderly women in community-dwelling group GDS are negatively correlated with chair sit and reach test, whilst elderly women in institutionalized group GDS is negatively correlated with 30-sec arm curl. It was concluded that greater upper limb strength reduce depression in institutionalized elderly women and greater lower limb flexibility reduce depression in community-dwelling elderly women. In summary, depression rate of institutionalized elderly women was proved to be higher than the community-dwelling elderly women.